2007 IEEE/ICME International Conference on Complex Medical Engineering 2007
DOI: 10.1109/iccme.2007.4381938
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Low-frequency Ultrasound to Enhance Transdermal Drug Delivery

Abstract: Low-frequency ultrasound(20 kHz Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Ultrasound also causes bulk fluid streaming and micro-streaming (Cui et al 2007; Lighthill 1987). It has been shown that enhancement of drug delivery through the skin using ultrasound can be due to streaming (Mitragotri et al 1995; Tang et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound also causes bulk fluid streaming and micro-streaming (Cui et al 2007; Lighthill 1987). It has been shown that enhancement of drug delivery through the skin using ultrasound can be due to streaming (Mitragotri et al 1995; Tang et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, medical researchers have shown that low-frequency ultrasound is effective in enhancing transdermal transport of various molecules [1,10,11,16,17,19]. Within this work, they have demonstrated that the frequencies around 40 kHz have excellent transdermal propagation with minimal heating [17].…”
Section: Related Workmentioning
confidence: 89%
“…The main mechanism of action in US‐enhanced drug delivery appears to be cavitation‐induced production of micrometer‐size pores in the surface barrier layer . Ultrasound also causes microstreaming and bulk fluid streaming . Streaming is caused by a reduction in the strength of the US waves due to their absorption and scattering .…”
mentioning
confidence: 99%
“…13,14 Ultrasound also causes microstreaming and bulk fluid streaming. 15 Streaming is caused by a reduction in the strength of the US waves due to their absorption and scattering. 16 Microstreaming is the flow of fluids caused by the application of US.…”
mentioning
confidence: 99%